HUBUNGAN KEMAMPUAN FUNGSIONAL DENGAN RISIKO JATUH PADA LANSIA DI POSYANDU LANSIA PUSKESMAS ABIANSEMAL II BADUNG - Putu Anggitha Surya Paramitha; Susy Purnawati (E-Jurnal Medika Udayana, 2017)
Falls is a problem that often occurs in elderly as a result of the decline in body function associated with aging. Functional abilities of elderly in performing daily activities is one of the factors that affect the risk of falls in elderly. The purpose of this study was to determine the correlation of functional abilities and risk of falls among the elderly in Integrated Health Services for Elderly of The Central Health Society Abiansemal II Badung Regency. The design of this study was observational analytic study with cross-sectional approach to the 107 elderly. Sampling was done by consecutive sampling. Data about functional abilities and the risk of falls are collected using a questionnaire. The results of this questionnaire are presented in tabular form and tested with Chi-Square statistical test. The results of the analysis with Chi-Square statistical tested obtained significance value (p) 0.000 that means there is a significant correlation between functional abilities and risk of falls among the elderly in Integrated Health Services for Elderly of The Central Health Society Abiansemal II Badung Regency. The level of the correlation of these two variables in this study are shown in contingency coefficient (r2) is 0.546. The direction of the correlation of these two variables is positive, which means more independence of functional abilities will make the elderly not at risk of falls. It can be concluded that there is a significant correlation between functional abilities and risk of falls among the elderly in Integrated Health Services for Elderly of The Central Health Society Abiansemal II Badung Regency. Elderly expected to be able to maintain their functional abilities and consider the factors that affect the risk of falling so they can minimize morbidity caused by falls. Keywords : Elderly, Functional Abilities, Risk of Falls